Development Of Image Compression Algorithms For Mammography Images - Abdul Karim, Mustafa Safa (2007)
In this research, a compression framework is proposed which possesses the desirable feature for mammogram compression. These features include the ability to support both lossless and lossy compression, low complexity, and flexibility in terms of the visual properties of the decompressed images. This framework overcomes the shortcomings of existing methods, and is used to design a complete compression system for mammograms. The framework is comprised of two stages.